Vision measurability and its impact on safe driving – a literature review - Thorslund, Birgitta; Strand, Niklas (Scandinavian Journal of Optometry and Visual Science, 2016)
Knowledge of measurability of vision and its impact on safe driving have proven to be important to secure a safe traffic system. Several different approaches to measure vision in order to improve road safety have been identified around the world. A trend seen in the literature is that traditional vision tests increasingly are supplemented by cognitive tests. The purpose of this study was to provide an overview of visual capabilities that are important for safe driving. The study answered questions about the visual capabilities that are essential for safe driving; which tests are available and how they are used; and existing evidence for these tests. The literature review was based on database searches of TRID, Web of Science and PubMed. In total 128 scientific publications were included in the overview. The results provided an overview of international standards of vision required for driving a car. Moreover, the results were structured according to the different visual capabilities and a corresponding account of the diseases that may affect these capabilities; which tests that are available and corroborating evidence for the test; and the manner in which these capabilities are important for safe driving. Two tests were highlighted based on the review and these were contrast sensitivity, and Useful Field of View. It was also concluded that 1), testing of vision should consist of several complementary tests, and 2), visual acuity is not sufficient for safe driving, and 3), tests including cognitive aspects can complement vision testing and improve the assessment of safe driving.